Development of a Portable Solar-Powered Ventilator with Bpm and Spo2 Monitoring System - Thiagarajan, Thineshan Raayar; Chua King Lee, (Evolution in Electrical and Electronic Engineering, 2024)
The goal of this work is to create a portable solar-powered ventilator with integrated beats per minute (BPM) and oxygen saturation (SpO2) monitoring. Although portable ventilators exist, there is a lack of solar-powered systems with patient health monitoring. This work involved designing, prototyping and testing a solar ventilator for rural healthcare. The input unit provides solar/adapter power, mode controls, and acquires data from a MAX30100 sensor. The processing unit contains an Arduino microcontroller and servo motor to actuate a breather mask. The output unit displays sensor measurements on an LCD and delivers air. Iterative simulation and prototyping refined the design. Testing demonstrated reliable 12-hour operation from solar panels and real-time patient monitoring. Integrated batteries accumulated excess daytime solar generation to enable sustained operation up to 4-5 hours. Rigorous testing assessed measurement accuracy across heart rates ranging 50-140 BPM along with SpO2 levels of 80-100%. Accuracy within BPM and SpO2 was +/- 3%, along with consistent signal integrity confirming reliable performance, this calculated by using the formula of Percent Error which is [(Sensor value - Oximeter value) / Oximeter value * 100%]. Outcomes indicate successful development of a solar-powered ventilator with integrated monitoring, validating potential to improve respiratory care through further improvements and clinical piloting.